HUBUNGAN GRIT DENGAN INTENSI BERWIRAUSAHA PADA PESERTA PROGRAM PEMBINAAN MAHASISWA WIRAUSAHA (P2MW) DI SEMARANG - Pramudyawardhani, Hilda Rosana; Ulya, Laila Listiana (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This research is motivated by the low entrepreneurial intention among university students despite having participated in an entrepreneurship development program. One psychological factor suspected to play a significant role in shaping entrepreneurial intention is grit, which is an individual's perseverance and resilience in achieving long-term goals. This study aims to determine the relationship between grit and entrepreneurial intention among university students participating in the P2MW program in Semarang. This study used a quantitative approach with a correlational design. The study subjects were 147 university students participating in the entrepreneurship development program, with data collection conducted through an online questionnaire. The results showed a strong and significant relationship between grit and entrepreneurial intention, with a correlation coefficient of 0.801, indicating that grit has an 80.1% correlation with students' entrepreneurial intention. Students with high levels of grit, characterized by perseverance, resilience in the face of obstacles, and consistent interest, tend to have stronger intentions to start, maintain, and develop a business. This study concludes that grit is an internal factor that plays a significant role in strengthening students' mental readiness and commitment to entrepreneurship. Therefore, grit development needs to be a priority in the implementation of entrepreneurship development programs to encourage the sustainability of student businesses after the program ends. Keyword: Grit, Entrepreneurial Intention, P2MW Student Participant. Abstrak: Penelitian ini dilatarbelakangi oleh rendahnya intensi berwirausaha di kalangan mahasiswa meskipun telah mengikuti program pembinaan kewirausahaan. Salah satu faktor psikologis yang diduga berperan penting dalam membentuk niat berwirausaha adalah grit, yaitu ketekunan dan ketangguhan individu dalam mencapai tujuan jangka panjang. Penelitian ini bertujuan untuk mengetahui hubungan antara grit dan intensi berwirausaha pada mahasiswa peserta P2MW di Semarang. Penelitian ini menggunakan pendekatan kuantitatif dengan desain korelasional. Subjek penelitian berjumlah 147 mahasiswa peserta program pembinaan kewirausahaan, dengan pengumpulan data dilakukan melalui kuesioner daring. Hasil penelitian menunjukkan adanya hubungan yang kuat dan signifikan antara grit dan intensi berwirausaha, dengan nilai koefisien korelasi sebesar 0,801, yang mengindikasikan bahwa grit memiliki keterkaitan sebesar 80,1% terhadap intensi berwirausaha mahasiswa. Mahasiswa dengan tingkat grit yang tinggi, ditandai oleh ketekunan, ketahanan menghadapi hambatan, dan konsistensi minat, cenderung memiliki niat yang lebih kuat untuk memulai, mempertahankan, dan mengembangkan usaha. Penelitian ini menyimpulkan bahwa grit merupakan faktor internal yang berperan penting dalam memperkuat kesiapan mental dan komitmen mahasiswa terhadap kewirausahaan, sehingga pengembangan grit perlu menjadi perhatian dalam pelaksanaan program pembinaan kewirausahaan guna mendorong keberlanjutan usaha mahasiswa setelah program berakhir. Kata kunci: Grit, Intensi Berwirausaha, Program Pembinaan Mahasiswa Wirausaha (P2MW).